The conductivity and dielectric studies of polymer electrolytes based on iota-carrageenan with sodium iodide and 1-butyl-3-methylimidazolium iodide for the dye-sensitized solar cells - Sugumaran, Thivagar; Silvaraj, D.S.; Saidi, Norshahirah M.; Farhana, N.K.; Ramesh, Subramaniam; Ramesh, Kasi; Ramesh, Singh (Springer Verlag (Germany), 2019)
Gel polymer electrolytes (GPE) were prepared with iota-carrageenan, sodium iodide (NaI), and 1-butyl-3-methylimidazolium iodide (BMIMI). The enhancement of ionic conductivity has achieved from 1.34 × 10 −2 S cm −1 to 2.11 × 10 −2 S cm −1 after the addition of BMIMI. The dielectric studies show that the dielectric constant increases with increasing concentration and temperature. The modulus studies show that ionic conductivity is dominant in the GPE samples. The XRD analysis shows that 30 wt.% BMIMI (IL30) has the optimum amorphous nature, and the combination of crystalline salt and semi crystalline polymer with amorphous ionic liquid gives a better amorphous nature. The FTIR studies confirm that there is complexation occurs between the iota-carrageenan, NaI, and BMIMI. Dye-sensitized solar cells (DSSC) were fabricated using the prepared GPE samples and characterized using photovoltaic studies. DSSC with IL30 sample shows the highest photovoltaic efficiency of 0.72%. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.